Analisis Perjanjian Perkawinan Menurut Undang-Undang Perkawinan Di Indonesia: (Studi Putusan Mahkamah Konstitusi Nomor 69/PUU-XIII/2015) - Faradilla Asyatama; Fully Handayani Ridwan (Universitas Serang Raya, 2021)
The protection of individual rights in marital relations according to positive Indonesian Law can be enforced by making a Prenuptial Agreement. Article 147 of the Civil Code states that a prenuptial agreement must be made before the marriage and must be in the form of a notarial deed which can apply to third parties since it registrates at the local District Court Registrar’s Office and has been recorded on Marriage Deed in the Civil Registry. In Indonesia, there has been unification in the field of Marriage Law, which has resulted in several changes to the provisions of prenuptial agreement. This study is aimed at obtaining answers to the following problems: (1) How is the binding force of the prenuptial agreement after the enactment of Law Number 1 of 1974? (2) What is the concept of making a prenuptial agreement after the decision of Constitutional Court Number 69/PUU-XIII/2015? Solving this problem is persued by empirical normative legal research methods using secondary data. The results of this study are: (1) A prenuptial agreement’s strength of binding after the enactment of the Marriage Law is after it is registered and ratified by a Marriage Registrar, and the content of prenuptial agreement is broader, not only coveting wealth; (2) The prenuptial agreement after the decision of Constitutional Court Number 69/PUU-XIII/2015 can be made after the marriage.